FACTORS AFFECTING SMARTPHONE ADDICTION IN CHILDREN - Mawaddah Nasution (Proceeding International Seminar of Islamic Studies, 2021)
Using the smartphones is very important for everyone, not only limited to adults but also children. Given the current conditions that are currently in a period of a pandemic, the government calls for a learning process from home. Likewise, adults who work from home to reduce the impact of covid transmission 19. All government policies that require people to work or study from home inevitably make most people have to use smartphones to work or to carry out the learning process. This makes people not separated from smartphones and certainly will have a serious impact on the lives of individuals, especially children, which can lead to smartphone addiction (smartphone addiction). Smartphone addiction is a smartphone attachment behavior accompanied by a lack of control and harms the individual. Children who have the task of developing learning while playing at their age, are currently losing playing time, and are only busy with smartphones to do their playing activities because from smartphones there are many interesting things or content that can make children feel at home and take a long look at the spectacle on their smartphone Keywords: Smartphone addiction, family, parents.